Pengaruh Produk Financing terhadap Tingkat Profitabilitas pada Bank Umum Syariah di Indonesia Periode Tahun 2015-2018 - Erawati, Teguh; Suryanti, Suryanti (Jurnal Ilmiah Akuntansi dan Humanika, 2019)
The purpose of this research is to analyze the effect of financing products on the level of profitability of Islamic commercial banks in Indonesia in the 2015-2018 period. The sample in this study used 11 Islamic banks registered at Bank Indonesia for the period of 2015-2018 taken using the purposive sampling method. These factors can then be tested using a significance of 0.05. The results of this study identify that mudharabah financing, musyarakah financing, and ijarah financing have a positive and significant effect on the profitability level of Islamic commercial banks.